Intra-articular injections with Carboxymethyl-Chitosan in patients affected by knee osteoarthritis non-responders to hyaluronic acid: a pilot study - Nicola Manocchio; Concetta Ljoka; Nicolò Piacentini; Roberto Sorge; Giulia Vita; Calogero Foti (European Journal of Translational Myology)
Osteoarthritis (OA) is a disabling disease that causes pain and functional limitation. OA symptoms can be treated with intra-articular injections of anti-inflammatory, viscosupplementary, or viscoinductive products. Non-responders to these approaches have limited options, often surgical (e.g. knee replacement). This retrospective study aims to evaluate the efficacy of a single injection of Carboxymethyl-Chitosan for advanced (Kellgren-Lawrence ≥3) and symptomatic knee OA in non-responders to hyaluronic acid. We enrolled 10 patients (5 female, 5 male). Treatment efficacy was assessed through the Visual Analogue Scale (VAS, pain) and the Knee Injury and Osteoarthritis Outcome Score (KOOS, knee function). Data are acquired from rating scales were administered at the time of injection (T0), one month (T1), three months (T2), and six months (T3) after treatment as for clinical practice. Results showed a significant improvement in pain and function at T1, with a subsequent gradual resumption of symptoms. In conclusion, the treatment showed a better outcome in the short term (i.e. up to 1 month after treatment); however, raw values of VAS and KOOS did not return to baseline levels showing a maintenance of improvement albeit not statistically significant.